Data from: Machine learning identifies ecological selectivity patterns across the end-Permian mass extinction - Foster, William; Ayzel, Georgy; Münchmeyer, Jannes; Rettelbach, Tabea; Kitzmann, Niklas; Isson, Terry; Mutti, Maria; Aberhan, Martin (Zenodo, 2021)
The end-Permian mass extinction occurred alongside a large swathe of environmental changes that are often invoked as extinction mechanisms, even when a direct link is lacking. One way to elucidate the cause(s) of a mass extinction is to investigate extinction selectivity as it can reveal critical information on organismic traits as key determinants of extinction and survival. Here we show that machine learning algorithms, specifically gradient boosted decision trees, can be used to identify determinants of extinction as well as predict extinction risk. To understand which factors led to the end-Permian mass extinction during an extreme global warming event, we quantified the ecological selectivity of marine extinctions in the well-studied South China region. We find that extinction selectivity varies between different groups of organisms and that a synergy of multiple environmental stressors best explains the overall end-Permian extinction selectivity pattern. Extinction risk was greater for genera that had a low species richness, had narrow bathymetric ranges limited to deep-water habitats, had a stationary mode of life, possessed a siliceous skeleton or, less critically, had calcitic skeletons. These selective losses directly link the extinction to the environmental effects of rapid injections of carbon dioxide into the ocean-atmosphere system, specifically the combined effects of expanded oxygen minimum zones, rapid warming, and potentially ocean acidification. : Funding provided by: Geo.X* Crossref Funder Registry ID: Award Number: SO_087_GeoX